Crack Propagation in Concrete under Compression - Tasdemir, M. A.; Maji, A. K.; Shah, S. P. (American Society of Civil Engineers (ASCE), 1990)
Mixedmode crack initiation and propagation starting from the aggregatematrix interface in concrete under uniaxial compression was investigated using fracture mechanics approach, finite element mode...